Telemedicine in community shelters: possibilities to improve chronic care among people experiencing homelessness in Hungary - Sándor Békási; Edmond Girasek; Zsuzsa Győrffy (BMC, 2022)
Abstract Background Digital health has expanded during the COVID-19 pandemic, while the exclusion of vulnerable populations with limited access to these technologies widens the gap to receive proper care. There is very little data available on the feasibility of telemedicine solutions regarding the chronic care of homeless persons. Methods In our study, 75 participants experiencing homelessness were recruited from four social institutions in Budapest, Hungary. The telecare pilot service consisted of six online consultations with a physician and was available in shelters biweekly. Self-developed questionnaires were used after every online session on the originating and remote sites as well, while a follow-up study was also completed among patients after four to six months of pilot closure. Parameters as frequencies, averages, and percentage distributions were analyzed and two linear regression models were built on explaining the doctors' and patients' overall rating of visits. Results During the pilot, 92.2% (n = 415) of originally planned visits were delivered and 55 clients (73.3%) attended the full program. Both the patients' and physicians' overall satisfaction was very high (4.52 and 4.79, respectively, on a 5-point Likert scale) and the patients' overall rating remained similarly high during the follow-up. Comparing the first and sixth visits, physicians reported significant improvements in almost all aspects. The linear regression models proved that confidence in the patients' assessment and diagnosis had the most prominent effect on the physicians' overall rating, while ease of use and lack of communication gaps influenced positively the patients' rating. Conclusion The results suggest that telehealth services represent a promising tool to ensure better care continuity while using shelter infrastructure and on-site assistance might reduce the digital exclusion of people experiencing homelessness.